2018
DOI: 10.2106/jbjs.17.00428
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Glenohumeral Arthrodesis

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 18 publications
0
40
1
4
Order By: Relevance
“…In Chammas cohort, 26 of 27 had improved satisfaction and all had gone on to union [15]. Wagner, et al demonstrated reasonable pain relief and improved shoulder stability in their cohort [7]. Atlan reports a 94% fusion rate [11].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In Chammas cohort, 26 of 27 had improved satisfaction and all had gone on to union [15]. Wagner, et al demonstrated reasonable pain relief and improved shoulder stability in their cohort [7]. Atlan reports a 94% fusion rate [11].…”
Section: Discussionmentioning
confidence: 95%
“…Patients having shoulder arthrodesis for recurrent instability tend to have worse outcomes than those having arthrodesis for other indications [7]. Thangarajah, et al looked at a cohort of six young epileptic patients who had recurrent instability attributed to seizures [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations